2016
DOI: 10.2174/1568009616666151112122126
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Epithelial-Mesenchymal Transition by E3 Ubiquitin Ligases and Deubiquitinase in Cancer

Abstract: Epithelial-mesenchymal transition (EMT) plays an important role in the development of tumor metastases by facilitating cell migration and invasion. One of the hallmarks of EMT is the diminished expression of E-cadherin and gain of mesenchymal traits, which are regulated by core EMT-inducing transcriptional factors (EMT-TFs), such as Snail/Slug, ZEB1/ZEB2, and Twist1. EMT-TFs are known to be extremely labile proteins, and their protein levels are tightly controlled by the ubiquitin-proteasome system (UPS). Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…USP22 is positively associated with invasion and metastasis of thyroid cancer by altering EMT expression . EMT‐inducing transcriptional factors are extremely labile proteins and tightly regulated by the ubiquitin–proteasome system, which indicates the important role of USPs in controlling EMT . In this study, we showed that USP32 depletion significantly decreased the migration ability of SCLC cells accompanied by increased E‐cadherin and decreased N‐cadherin expression.…”
Section: Discussionmentioning
confidence: 57%
“…USP22 is positively associated with invasion and metastasis of thyroid cancer by altering EMT expression . EMT‐inducing transcriptional factors are extremely labile proteins and tightly regulated by the ubiquitin–proteasome system, which indicates the important role of USPs in controlling EMT . In this study, we showed that USP32 depletion significantly decreased the migration ability of SCLC cells accompanied by increased E‐cadherin and decreased N‐cadherin expression.…”
Section: Discussionmentioning
confidence: 57%
“…S5). These genes did not emerge as differentially expressed by transcriptome sequencing analysis, but their protein product is known to undergo posttranscriptional regulation (12,13).…”
Section: Molecular Profiling Of Dfsp Evolutionmentioning
confidence: 93%
“…It is now generally appreciated that EMT occurs during cancer cell progression and metastasis. 2,3 The EMT is a central process of embryogenesis or normal cell development, in which epithelial (E) cells reach fibroblast-like mesenchymal (M) state. In brief, the fairly round shaped E cells are connected by cell–cell adhesion, facilitating cell layer formation and remain largely static.…”
Section: Resultsmentioning
confidence: 99%
“…1 Recent works have shown that cancers can evolve non-genetically and are able to make the epithelial-mesenchymal transition (EMT), providing with high motility to form metastasis of surrounding and other far-from-connected tissues. 2,3 It is, therefore, conceivable why most, if not all, invasive and non-invasive treatment strategies, based on the predominant “average cell” (all cells being equal) approach, to tackle and control the complexity of cancer succumb to cell proliferations. To understand the complexities of dynamic cancer response, and to regulate them successfully, experimental approaches alone are insufficient.…”
Section: Introductionmentioning
confidence: 99%